2020
DOI: 10.4269/ajtmh.19-0554
|View full text |Cite|
|
Sign up to set email alerts
|

Efficacy of a Spatial Repellent for Control of Malaria in Indonesia: A Cluster-Randomized Controlled Trial

Abstract: A cluster-randomized, double-blinded, placebo-controlled trial was conducted to estimate the protective efficacy (PE) of a spatial repellent (SR) against malaria infection in Sumba, Indonesia. Following radical cure in 1,341 children aged ³ 6 months to £ 5 years in 24 clusters, households were given transfluthrin or placebo passive emanators (devices designed to release vaporized chemical). Monthly blood screening and biweekly human-landing mosquito catches were performed during a 10-month baseline (June 2015-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
82
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 63 publications
(89 citation statements)
references
References 49 publications
1
82
0
Order By: Relevance
“…It contains transfluthrin, a volatile pyrethroid chemical currently used in household mosquito control product such as coils. Preliminary findings of a robust cluster randomized, double-blinded placebo-controlled trial in Indonesia suggests protective effects of the SR product evaluated in this study [17].…”
Section: Sr Productmentioning
confidence: 66%
See 1 more Smart Citation
“…It contains transfluthrin, a volatile pyrethroid chemical currently used in household mosquito control product such as coils. Preliminary findings of a robust cluster randomized, double-blinded placebo-controlled trial in Indonesia suggests protective effects of the SR product evaluated in this study [17].…”
Section: Sr Productmentioning
confidence: 66%
“…Studies in Africa have shown that increasing knowledge and awareness of vector control tools may increase the uptake of novel malaria control interventions [16,17]. Repellent products such as mosquito coils, topical repellent creams and spatial repellent emanators have been proven effective to protect against malaria [18][19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…Our results support SRs as a flexible class of vector control products with positive public health impact not limited to ABV diseases. Transfluthrin- 15 and metofluthrinbased 16,25 mosquito coils have been shown to reduce malaria and the same spatial repellent device used in our Iquitos trial reduced malaria infections in an Indonesia cRCT. 15 Together, these results highlight the potential for SRs to reduce a variety of vector-borne diseases, augment existing public health efforts and be an effective component of vector control intervention strategies.…”
mentioning
confidence: 67%
“…Our intervention was a transfluthrin passive emanator designed and produced by SC Johnson (Racine, WI), replaced at 2-week intervals, as described previously ( Figure S1, SI Section 1.3.2). 16 Spatial repellent and placebo intervention had identical packaging and were deployed in houses by study personnel using a blinded coding scheme. The placement of the intervention followed manufacturer specifications for indoor use conditions.…”
Section: Randomization and Interventionmentioning
confidence: 99%
“…These data emphasize the need for new tools, such as spatial [51] or topical repellents, as well as new research that evaluates novel paradigms directed at residual transmission occurring outside the functional scope of present interventions, accelerating progress towards elimination.…”
Section: Discussionmentioning
confidence: 94%